2017
DOI: 10.15255/kui.2016.002
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production by Transesterification of Tallow Fat Using Heterogeneous Catalysis

Abstract: Biodiesel is an eco-friendly alternative diesel fuel prepared from domestic renewable resources i.e. vegetable oils and animal fats. In this process, biodiesel is produced by transesterification of triglycerides present in animal fat or vegetable oils, by displacing glycerine with a low molar mass alcohol using homogeneous or heterogeneous catalysis. The resulting ester, after mixing with diesel fuels, has physicochemical properties similar to those of conventional fuels. In this work, the batch process of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…301,309 The conversion of tallow fat with methanol showed the yield of methyl and ethyl esters around 95% using Amberlyst-A26 OH with reaction conditions, like a tallow fat-tomethanol molar ratio of 6 : 1, and a resin loading of 2 mol L À1 at 65 C temperature for about 8.5 hours. 310 Hartono et al 311 investigated the catalytic efficacy of a heterogeneous catalyst obtained from a different source, like Lewatit macroporous resin, Amberlite gel resin and natural zeolite from Bayah, to transform WCO to biodiesel. Authors reported the 85.94% yield of biodiesel production by Lewatit macroporous anion exchanger with 6 M NaOH.…”
Section: Acid Catalystsmentioning
confidence: 99%
“…301,309 The conversion of tallow fat with methanol showed the yield of methyl and ethyl esters around 95% using Amberlyst-A26 OH with reaction conditions, like a tallow fat-tomethanol molar ratio of 6 : 1, and a resin loading of 2 mol L À1 at 65 C temperature for about 8.5 hours. 310 Hartono et al 311 investigated the catalytic efficacy of a heterogeneous catalyst obtained from a different source, like Lewatit macroporous resin, Amberlite gel resin and natural zeolite from Bayah, to transform WCO to biodiesel. Authors reported the 85.94% yield of biodiesel production by Lewatit macroporous anion exchanger with 6 M NaOH.…”
Section: Acid Catalystsmentioning
confidence: 99%
“…OH with reaction conditions like tallow fat with methanol molar ratio of 6:1, resin loading of 2 mol/L at 65 °C temperature for about 8.5 hours. 310 Hartono et al 311 and catalyst load (20 wt. %).…”
Section: Ion Exchange Resinmentioning
confidence: 99%
“…The result of this investigation was a biodiesel yield of 90-95 % after 360 min. 11 Melnyk et al demonstrated the possibility of using CU-2-8 cation exchange resin with immobilized metal ions as catalysts for transesterification of vegetable oils. 12 Under the optimal conditions, in the presence of the best catalysts, when using ethanol, the triglycerides conversion was more than 99 %, and when propan-1-ol was used, the conversion exceeded 97 %.…”
Section: Introductionmentioning
confidence: 99%